Maintenance System of Universal Goss Printing Machine based on failure data using RCM and RCS method - Alhilman, Judi (School of Industrial Engineering, Telkom University, 2018)
OverBased on RCM analysis for each critical subsystem obtained interval preventive maintenance for transfer roller 127.60 hours, Ink fountain roller 24.45 hours, ink form roller 29.23 hours respectively, and the wash-up device is no scheduled maintenance. For spare parts inventory strategies the result using RCS method are: transfer roller104 units, ink fountain roller requires 32 units, ink form roller 36 units and are holding spare policy required, and a wash-up device no holding spare parts.   Inserted: r   Inserted: u   Inserted: ng   Inserted: foll   Inserted: polic   Inserted: d   Inserted: the   Deleted:in acc   Deleted:rdance   Deleted:th   Deleted:i   Deleted: accor   Deleted:anc   Deleted: with   Deleted:strateg